Preparation method of high-strength low-carbon constructional column formwork
By preparing high-strength and low-carbon structural column mold shells, the high carbonization activity of low-heat cement and industrial solid waste is used to absorb industrial emissions of CO2, which solves the problems of limited CO2 diffusion and industrial solid waste expansion and collapse in mineralization reactions, and achieves high-strength, low-carbon and environmentally friendly building materials products.
Patent Information
- Application Number
- CN202510055149.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
AI Technical Summary
In the prior art, during the mineralization reaction of traditional cement-based materials, the mineralization of C3S minerals is limited to the surface, hindering the diffusion of CO2 and affecting the progress of the mineralization reaction. At the same time, industrial solid waste is prone to expand and crumble during the press-evaporation process without carbonation.
A high-strength and low-carbon structure column mold shell is prepared by mixing low-heat cement, steel slag, or mineral powder, quartz sand and other raw materials, pouring and forming, dry maintenance, dry maintenance and CO2 carbonization maintenance are carried out, and the high carbonization activity of β-C2S and γ-C2S is used to absorb industrial emissions to form CaCO3, thereby improving the strength and stability of the material.
It has realized the resource utilization of industrial solid waste and permanent carbon sequestration, improved the strength and stability of structural column mold shells, reduced CO2 emissions, and reduced the use of traditional cement and carbon emissions.
Smart Images

Figure CN119841586A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building component preparation, in particular to a method for preparing a high-strength and low-carbon structural column formwork. Background Art
[0002] The carbonization principle of cement-based materials is that cement and its hydration products react with CO2. CO2 sequestration is achieved by supplying CO2 to cement-based materials during the production process. Existing studies have shown that CO2 treatment can accelerate the development of the strength of silicate cement, and under appropriate humidity conditions, it can also rapidly react with calcium silicate minerals. With subsequent in-depth research, it was found that in the traditional hydration process, C3S minerals are considered to be superior to C2S mineral components due to their higher hydration activity and early strength performance. However, during the mineralization reaction, the mineralization of C3S is limited to the surface, which hinders the subsequent diffusion of CO2 and affects the mineralization reaction. The carbonization depth of C2S mineral components is much greater than that of C3S, and a large amount of calcium carbonate and high-polymerization silica gel are formed. At the same time, the study also shows that high belite cement (low heat cement) with β-C2S as the main mineral phase has good carbonization reaction ability, and the mineralization reaction strength and pore structure of its products are far superior to those of ordinary silicate cement products.
[0003] Industrial solid waste (steel slag, carbide slag, slag, fly ash, waste lime, coal fly ash and waste incinerator ash, etc.) can also produce mineralization reactions similar to cement. Among them, the high content of f-CaO and f-MgO in steel slag is very likely to cause poor volume stability. However, f-CaO and f-MgO have high carbonation activity. During the carbonation curing process, the content of f-CaO and f-MgO can be greatly reduced to a safe range for use.
[0004] During the autoclave process, the steel slag specimens that have not been cured by carbonation will form Ca(OH)2 and Mg(OH)2, and expand, causing the steel slag specimens to collapse completely after autoclave. Studies have shown that after 2 hours of carbonation curing, the volume stability can be greatly improved. Compared with the steel slag that has not been cured by carbonation, the content of Ca(OH)2 is reduced, especially the content of Mg(OH)2 is significantly reduced, indicating that f-CaO and f-MgO have high carbonation activity and are rapidly digested during the carbonation process, thereby improving the volume stability of the steel slag. At the same time, minerals such as β-C2S and C3S in the steel slag will form CSH gel during the carbonation process. CSH has a large specific surface area and van der Waals force, which can further improve the strength of steel slag products after carbonation. The use of slag in the mineralization process is beneficial to improving the strength of concrete and resisting deicing salt. Studies have shown that concrete mixed with slag can absorb 15.1% of CO2 after 4 hours of mineralization, and has higher mechanical properties than concrete mixed with solid wastes such as fly ash and red mud. This is mainly because the growth of mineralization products in concrete mixed with mineral powder is more orderly, which has a positive effect on the increase in strength.
[0005] As an important component of the building materials industry, cement accounts for 40.8% of the carbon emissions of building materials. As the second largest man-made material in the world, cement is mostly used in its production. Concrete is traditionally 2350kg / m 3 Calculated, the carbon emission factor is 0.12-0.16 kgCO2 / m 3 The huge output has brought about huge carbon emissions and natural resource consumption. Summary of the invention
[0006] The technical problem to be solved by the present invention is: in order to overcome the deficiencies in the prior art, a method for preparing a high-strength and low-carbon structural column formwork is provided.
[0007] The technical solution adopted by the present invention is: a method for preparing a high-strength and low-carbon structural column formwork, and the process steps are as follows:
[0008] A. Mix the raw materials of low-heat cement, steel slag or mineral powder, and quartz sand, add water and water reducing agent for mixing, and cast the mixed slurry in a mold, wherein the weight ratio of the raw materials is: 50-70% of low-heat cement, 10-50% of steel slag or mineral powder, the water-binder ratio is 0.2-0.3, and the mass ratio of the total mass of low-heat cement, steel slag or mineral powder to quartz sand is 3:5;
[0009] B. Move the structural column formwork formed in step A into a dry curing room at a temperature of 26° C. for curing, and remove the mold after curing for 24 hours;
[0010] C. Move the structural column formwork after demolding in step B into a 40°C blast drying oven for drying and curing for 10-12 hours;
[0011] D. Move the structural column formwork dried in step C into a carbonization kettle at 30±3°C for CO2 carbonization curing for 6-48h, and then move the carbonized structural column formwork into a standard curing box to obtain a high-strength and low-carbon structural column formwork;
[0012] Specifically: put the column mold shell after drying in step C into the carbonization kettle, first evacuate the vacuum, and introduce CO2 when the vacuum degree is -0.95MPa. When the pressure of CO2 introduced into the kettle is -0.55MPa, introduce air to normal pressure 0, and then close the air valve. The CO2 concentration is read to be about 30% at this time, and then adjust the CO2 ventilation valve rate to 1, and the air valve rate to 2.3 to simulate the recovery and utilization of CO2 tail gas emitted by industry. The CO2 concentration is controlled at 30vol%, and the curing time is 12-48h. Then move the carbonized mold shell into a standard curing box with a temperature of (20±2)℃ and a humidity ≥95% for standard curing to ensure that the structural column mold shell is fully carbonized.
[0013] Furthermore, the water reducing agent described in the present invention is a polycarboxylic acid-based water reducing agent, and the fluidity of the mortar is controlled at 180-240 mm according to the fluidity of the mortar on site.
[0014] Furthermore, the thickness of the structural column formwork blank after demolding in step B of the present invention is 10 mm.
[0015] Furthermore, the C2S content in the low-heat cement of the present invention is greater than 40%. On the one hand, the low-heat cement provides a certain early strength for the cast gel. On the other hand, the calcium silicate minerals in the low-heat cement will undergo carbonation reactions to varying degrees, especially β-C2S has a strong carbonation activity.
[0016] Furthermore, the steel slag described in the present invention is steel slag particles obtained after hot stuffing, screening, crushing, and magnetic separation to remove iron, and the main mineral phases are dicalcium silicate, tricalcium silicate, dicalcium ferrite, wurtzite, calcite, free calcium oxide, free magnesium oxide, calcium hydroxide and RO phase (solid solution of MgO, FeO and MnO, etc.), etc.
[0017] Green and low-carbon environmentally friendly building materials are made by the present invention. Carbonization technology is to place cement-based cementitious building materials in a CO2 gas environment and perform carbonization under certain temperature, humidity and pressure conditions, which can not only improve its early strength and increase the stability of the product, but also effectively solidify a large amount of industrial-grade CO2, realize the effective utilization of secondary resources, and thereby prepare prefabricated ring beam formwork, structural column formwork, infill wall prefabricated formwork and other building materials products with the advantages of high strength, low cost, good stability and the like.
[0018] Permanently fix carbon and reduce CO2 emissions. The cement industry and the steelmaking industry are both major industries that emit CO2 gas. Using steel slag with a certain activity and low-heat cement containing β-C2S with high carbonization activity to absorb CO2 in waste gas and prepare qualified building materials is an effective measure to improve the utilization rate of solid waste, reduce CO2 emissions, and reduce the production and use of cement clinker. It has great economic, environmental and social benefits. The source of industrial solid waste is usually also the main source of CO2 emissions and the source of a large amount of difficult-to-use low-value waste. Using industrial solid waste to fix carbon nearby and utilize solid waste resources not only saves transportation costs, but also makes full use of a large amount of difficult-to-use low-value waste heat to achieve the effect of accelerating carbonization, realizing efficient use of energy and permanent solidification of CO2.
[0019] β-C2S (β-calcium disilicate) and γ-C2S (γ-calcium disilicate) play an important role in the carbonation process of cement materials, and each has unique performance advantages. β-C2S stands out for its rapid carbonation reactivity, which makes it particularly effective in the process of reacting with CO2 to form CaCO3, thereby significantly improving the mechanical strength and durability of the material. This rapid reaction not only accelerates the sequestration of CO2, but also helps fill the pores of the material and enhances the material's resistance to environmental erosion. In contrast, the carbonization reaction rate of γ-C2S is slower, and this property makes it more suitable for applications that require a long-term carbonization process, such as continuous use in a low CO2 concentration environment, which can be carbonized more evenly and avoid the problem of local over-carbonization. In addition, γ-C2S has good thermal stability and is suitable for applications in high temperature environments, ensuring performance stability under extreme conditions.
[0020] In practical applications, both β-C2S and γ-C2S have high carbonization reaction activity. The different characteristics of the two provide a wide range of application possibilities for cement-based materials, from high-speed carbonization to long-term performance in specific environments, which reflects the unique value and importance of these two calcium silicate mineral phases.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] 1. A method for preparing a high-strength and low-carbon structural column formwork of the present invention realizes the resource utilization of industrial solid waste while realizing high-strength formwork mortar with permanent carbon fixation, utilizes a part of the early activity of low-heat cement, a hydraulic cementitious material, to provide demoulding strength, and utilizes steel slag or slag and low-heat cement with high carbonization activity of high belite mineral phase to carbonize the cementitious material; reduces the use of low-heat cement, improves the traditional natural hardening method of cement, and obtains a structural column formwork with high strength, low carbon and environmental protection.
[0023] 2. Mineral carbonation is an important part of CCUS. Mineral carbonation has become an important part of carbon emission reduction technology, especially steel slag. As a solid waste generated in the steelmaking process, steel slag carbonation (i.e., using steel slag to fix CO2) can use the by-product steel slag of the steel plant nearby and recycle the by-product waste gas CO2, so as to achieve the sustainable development goal of "waste treatment and recycling". Therefore, the steel slag carbon utilization products prepared by steel slag carbonization technology can not only effectively reduce the CO2 generated by large-scale high-carbon emission industrial processes, but also produce market-competitive green, low-carbon and environmentally friendly building materials;
[0024] 3. The low-heat cement used in the present invention has a high content of β-C2S and γ-C2S, which provide a series of significant structural and environmental advantages when preparing prefabricated components. First, the presence of these two calcium silicate phases significantly enhances the carbonation reaction ability of cement, which means that they can effectively react with CO2 in the atmosphere to form CaCO3. This reaction not only helps to seal CO2 and reduce greenhouse gas emissions, but also increases the density and mechanical strength of the material by filling the pores of cement. This enhanced density and strength make low-heat cement prefabricated components more superior in compression and bending resistance, increase the durability and life of the components, and thus reduce long-term maintenance costs. In addition, due to the low heat release of low-heat cement during the hydration process, large-volume prefabricated components using this cement reduce thermal stress and thermal cracking problems during the curing and hardening process, which is crucial to ensuring the integrity and stability of the structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a structural schematic diagram of the structural column formwork in the present invention;
[0026] Figure 2 It is a schematic diagram of the state of the structural column formwork in the present invention during construction application.
[0027] Numbers in the figure: 1. Wall, 2. Structural column formwork. DETAILED DESCRIPTION
[0028] The embodiments of the present invention are described in detail below. The embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.
[0029] The present invention provides a method for preparing a high-strength and low-carbon structural column formwork, and the process steps are as follows:
[0030] A. Mix the raw materials of low-heat cement, steel slag or mineral powder, and quartz sand, add water and water reducing agent for mixing, and cast the mixed slurry in a mold, wherein the weight ratio of the raw materials is: 50-70% of low-heat cement, 10-50% of steel slag or mineral powder, the water-binder ratio is 0.2-0.3, and the mass ratio of the total mass of low-heat cement, steel slag or mineral powder to quartz sand is 3:5;
[0031] B. Move the structural column formwork formed in step A into a dry curing room at a temperature of 26° C. for curing, and remove the mold after curing for 24 hours;
[0032] C. Move the structural column formwork after demolding in step B into a 40°C blast drying oven for drying and curing for 10-12 hours;
[0033] D. Move the structural column formwork dried in step C into a carbonization kettle at 30±3°C for CO2 carbonization curing for 6-48h, and then move the carbonized structural column formwork into a standard curing box to obtain a high-strength and low-carbon structural column formwork;
[0034] Specifically: put the column mold shell after drying in step C into the carbonization kettle, first evacuate the vacuum, and introduce CO2 when the vacuum degree is -0.95MPa. When the pressure of CO2 introduced into the kettle is -0.55MPa, introduce air to normal pressure 0, and then close the air valve. The CO2 concentration is read to be about 30% at this time, and then adjust the CO2 ventilation valve rate to 1, and the air valve rate to 2.3 to simulate the recovery and utilization of CO2 tail gas emitted by industry. The CO2 concentration is controlled at 30vol%, and the curing time is 12-48h. Then move the carbonized mold shell into a standard curing box with a temperature of (20±2)℃ and a humidity ≥95% for standard curing to ensure that the structural column mold shell is fully carbonized.
[0035] Among them, the water reducer is a polycarboxylic acid-based water reducer, and the mortar fluidity is controlled at 180-240mm based on the on-site mortar fluidity.
[0036] The thickness of the structural column shell blank after demolding in step B is 10 mm.
[0037] The content of C2S in low heat cement is greater than 40%. On the one hand, low heat cement provides a certain early strength for the cast cement. On the other hand, the calcium silicate minerals in low heat cement will undergo carbonation reaction to varying degrees, especially β-C2S has a strong carbonation activity.
[0038] Steel slag is steel slag particles obtained after hot stuffing, screening, crushing and magnetic separation to remove iron. The main mineral phases are dicalcium silicate, tricalcium silicate, dicalcium ferrite, wurtzite, calcite, free calcium oxide, free magnesium oxide, calcium hydroxide and RO phase (solid solution of MgO, FeO and MnO, etc.).
[0039] The invention discloses a method for preparing a high-strength and low-carbon structural column formwork, which realizes resource utilization of industrial solid waste and realizes high-strength formwork mortar with permanent carbon fixation, utilizes a part of the early activity of low-heat cement, a hydraulic cementitious material, to provide demoulding strength, and utilizes steel slag or slag and low-heat cement with high carbonization activity of high belite mineral phase to carbonize the cementitious material; reduces the use of low-heat cement, improves the traditional natural hardening method of cement, and obtains a structural column formwork with high strength, low carbon and environmental protection.
[0040] In construction, the advantages of using high-strength and low-carbon structural column formwork are summarized as follows (such as Figure 1 and 2 shown):
[0041] (1) Save labor and time: By prefabricating cavity formwork blocks and the upper and lower interlocking assembly method, the structural column formwork 2 and the secondary masonry can be built in the wall 1 at one time, eliminating the traditional formwork support and dismantling procedures, simplifying the construction process, saving a lot of time and labor costs, and improving construction efficiency.
[0042] (2) Improve structural stability: Use standardized ring beam prefabricated formwork concrete blocks and build the ring beam formwork in a fully assembled manner, so that the ring beam and structural columns are cast in one piece, eliminating the ring beam formwork support and removal process. This avoids quality problems caused by step-by-step construction, ensures the overall stability of the secondary masonry and structural columns, and improves the seismic performance of the building.
[0043] (3) Standardized production: In order to solve the problem of on-site cutting during the construction process, we cooperated with manufacturers to complete the design and production of a variety of prefabricated formwork blocks, realizing the standardization of the formwork, effectively reducing the complexity of the construction site, ensuring the accuracy of masonry, reducing material waste and process errors, and improving construction quality.
Claims
1. A method for preparing a high-strength and low-carbon structural column formwork, characterized in that: The process steps are as follows: A. Mix the raw materials of low-heat cement, steel slag or mineral powder, and quartz sand, add water and water reducing agent for mixing, and cast the mixed slurry in a mold, wherein the weight ratio of the raw materials is: 50-70% of low-heat cement, 10-50% of steel slag or mineral powder, the water-binder ratio is 0.2-0.3, and the mass ratio of the total mass of low-heat cement, steel slag or mineral powder to quartz sand is 3:5; B. Move the structural column formwork formed in step A into a dry curing room at a temperature of 26° C. for curing, and remove the mold after curing for 24 hours; C. Move the structural column formwork after demolding in step B into a 40°C blast drying oven for drying and curing for 10-12 hours; D. Move the structural column formwork dried in step C into a carbonization kettle at 30±3°C for CO2 carbonization curing for 6-48h, and then move the carbonized structural column formwork into a standard curing box to obtain a high-strength and low-carbon structural column formwork; Specifically: put the column mold shell after drying in step C into the carbonization kettle, first evacuate the vacuum, and introduce CO2 when the vacuum degree is -0.95MPa. When the pressure of CO2 introduced into the kettle is -0.55MPa, introduce air to normal pressure 0, and then close the air valve. The CO2 concentration is read to be about 30% at this time, and then adjust the CO2 ventilation valve rate to 1, and the air valve rate to 2.3 to simulate the recovery and utilization of CO2 tail gas emitted by industry. The CO2 concentration is controlled at 30vol%, and the curing time is 12-48h. Then move the carbonized mold shell into a standard curing box with a temperature of (20±2)℃ and a humidity ≥95% for standard curing to ensure that the structural column mold shell is fully carbonized.
2. The method for preparing a high-strength and low-carbon structural column formwork according to claim 1, characterized in that: The water reducer is a polycarboxylic acid-based water reducer, and the fluidity of the mortar is controlled at 180-240 mm according to the fluidity of the mortar on site.
3. The method for preparing a high-strength and low-carbon structural column formwork according to claim 1, characterized in that: The thickness of the structural column shell blank after demolding in step B is 10 mm.
4. The method for preparing a high-strength and low-carbon structural column formwork according to claim 1, characterized in that: The content of C2S in the low-heat cement is greater than 40%.
5. The method for preparing a high-strength and low-carbon structural column formwork according to claim 1, characterized in that: The steel slag is steel slag particles obtained after hot stuffing, screening, crushing and magnetic separation to remove iron.